Thromboplastin-thrombomodulin-mediated Time and Serum Folate Levels Are Genetically Correlated with the Risk of Thromboembolic Disease: Results from the GAIT Project - Souto, Juan Carlos; Almasy, Laura; Borrell, Montserrat; Stone, William H.; Blanco-Vaca, Francisco; Soria, José Manuel; Blangero, John; Fontcuberta, Jordi (Thrombosis and Haemostasis, 2002)
The GAIT (Genetic Analysis of Idiopathic Thrombophilia) Project is a family-based study dedicated to elucidating the genetic basis of hemostasis-related phenotypes and thrombosis risk. In this paper, we have examined several lesser-studied hemostasis-related phenotypes in the 21 GAIT families: levels of vitamin B12, serum folate, whole blood folate, α 2-antiplasmin, prekallikrein, β2-glycoprotein I, soluble P-selectin, factor XIII A and B subunits and a new coagulation measurement based on thromboplastin time in the presence or absence of thrombomodulin. Using the variance component method, we estimated the relative contributions of genetic and environmental influences on these phenotypes. In addition, we calculated the genetic correlations between thrombosis risk and each of these phenotypes.All 12 phenotypes showed significant genetic contributions with genes accounting for 22% to 78% of the variance after correction for covariate effects. Four phenotypes (three traits involving thromboplastin-thrombomodulin mediated coagulation time and serum folate) exhibited significant genetic correlations with thrombosis. Thus, some of the genes that influence quantitative variation in these physiological phenotypes also influence the risk of thrombosis.The high heritabilities and significant genetic correlations between thrombosis and some risk factors suggest that joint consideration of correlated quantitative phenotypes will aid in identifying susceptibility genes.
Keywords: Thrombosis; coagulation; genetics; family-based studies; heritability